Surgical clipping versus endovascular coiling for elderly patients presenting with subarachnoid hemorrhage. (26th August 2015) - Bekelis, Kimon; Gottlieb, Dan; Su, Yin; O'Malley, Alistair J; Labropoulos, Nicos; Goodney, Phillip; MacKenzie, Todd A
Abstract : Background: The comparative effectiveness of the two treatment options (surgical clipping and endovascular coiling) for ruptured cerebral aneurysms has not been studied in real-world practice in the USA. We investigated the association between the treatment method for ruptured cerebral aneurysms and outcomes. Methods: We performed a retrospective cohort study of elderly patients who underwent treatment for ruptured cerebral aneurysms from 2007 to 2012 using a 100% sample of Medicare fee-for-service claims data. An instrumental variable analysis was used to control for unmeasured confounding and to create pseudo-randomization on the treatment method. In sensitivity analysis, controlling only for measured confounding, we used propensity score conditioning and inverse probability weighting with mixed effects to account for clustering at the Hospital Referral Region (HRR) level. Results: During the study period 3210 patients underwent treatment for ruptured cerebral aneurysms and met the inclusion criteria. Of these, 1206 (37.6%) had surgical clipping and 2004 (62.4%) had endovascular coiling. Instrumental variable analysis demonstrated no difference between coiling and clipping in 1-year postoperative mortality (OR 1.04; 95% CI 0.70 to 1.54), likelihood of discharge to rehabilitation (OR 1.07; 95% CI 0.72 to 1.58), or 30-day readmission rate (OR 1.44; 95% CI 0.70 to 1.87). However, clipping was associated with 2.7 days longer length of stay (LOS) (95% CI 0.45 to 4.99). The same associations were present in propensity score adjusted and inverse probability weighted models. Conclusions: In a cohort of Medicare patients, we did not demonstrate a difference in mortality, rate of discharge to rehabilitation, and readmissions between clipping and coiling of ruptured cerebral aneurysms. Clipping was associated with a slightly longer LOS.